2003
DOI: 10.1002/rmv.405
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐dependent enhancement of viral infection: molecular mechanisms and in vivo implications

Abstract: Besides the common receptor/coreceptor-dependent mechanism of cellular attachment, some viruses rely on antiviral antibodies for their efficient entry into target cells. This mechanism, known as antibody-dependent enhancement (ADE) of viral infection, depends on the cross-linking of complexes of virus-antibody or virus-activated complement components through interaction with cellular molecules such as Fc receptors or complement receptors, leading to enhanced infection of susceptible cells. Recent studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
247
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(255 citation statements)
references
References 105 publications
3
247
0
1
Order By: Relevance
“…[17][18][19]. None of these mechanisms seemed to be involved in the enhancement of HCVpp infectivity, because the infectivity of pp was enhanced with chimpanzee serum but not with derivative IgG and, furthermore, heat-treated human serum (30 min at 65°C) still enhanced, suggesting that complement also was not involved.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19]. None of these mechanisms seemed to be involved in the enhancement of HCVpp infectivity, because the infectivity of pp was enhanced with chimpanzee serum but not with derivative IgG and, furthermore, heat-treated human serum (30 min at 65°C) still enhanced, suggesting that complement also was not involved.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, heterologous challenge of mice with CV-B3 after an initial infection with CV-B2 resulted in enhanced pathology 15,16 which especially can be due to the phenomenon of antibody-dependent enhancement. 15,17,18,19,9 Moreover it has been shown that in adult mice homologous challenge with CVB4-E2 resulted in hyperglycaemia, 20 and that challenge of pups of dams infected during pregnancy resulted in enhanced pathology in the offspring through possibly immune-mediated mechanisms due to pre-existing immunity. 21 In conclusion, in vitro assays displayed that serum samples of mice inoculated with CV-B4 E2 had an enhancing effect able to increase, on the one hand, the CV-B4 E2-induced production of antiviral mediators by spleen cells cultures and, on the other hand, the infection of these cells with CV-B4 E2.…”
Section: Discussionmentioning
confidence: 99%
“…A popular hypothesis is that DHF͞DSS results from antibody-dependent enhancement, whereby antibodies from a previous infection facilitate subsequent infection with a heterogeneous serotype (3). However, the exact mechanisms of pathogenesis remain contentious, and the potential for enhancement also may depend on the particular strain type (genotype) within the serotype and immunological differences within the host (4)(5)(6)(7). Theoretical studies of the potential impact of antibody-dependent enhancement on the epidemiology of dengue have shown that enhancement of transmission may generate cycles or chaotic oscillations in infection numbers (8), leading to an optimum degree of enhancement to prevent extinction (9), whereas enhancement of mortality may prevent immunologically similar serotypes from coexisting (10).…”
mentioning
confidence: 99%